2021
DOI: 10.1021/acsinfecdis.0c00744
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbe-Derived Outer Membrane Vesicles: A Potential Platform to Control Cecal Load of Campylobacter jejuni

Abstract: Acute diarrheal illness and gastroenteritis caused by Campylobacter jejuni infection remain significant public health risks in developing countries with substantial mortality and morbidity in humans, particularly in children under the age of five. Genetic diversities among Campylobacter jejuni and limited understanding of immunological correlations of host protection remain primary impediments for developing an effective measure to controlCampylobacter infection. Moreover, the lack of a reliable in vivo model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Bacterial-derived EVs appear to be candidates for mucosal vaccines causing immune protection against specific pathogens [ 47 , 48 , 49 ]. Accordingly, massive production of both intestinal sIgA as well as serum IgG antibodies against EV-transmitted antigens was noted in mice that were orally immunized with three doses of chitosan-coated Campylobacter jejuni -derived EVs together with the induction of a specific cell-mediated immune response.…”
Section: Bacterial Evs—another Source For Consideration?mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial-derived EVs appear to be candidates for mucosal vaccines causing immune protection against specific pathogens [ 47 , 48 , 49 ]. Accordingly, massive production of both intestinal sIgA as well as serum IgG antibodies against EV-transmitted antigens was noted in mice that were orally immunized with three doses of chitosan-coated Campylobacter jejuni -derived EVs together with the induction of a specific cell-mediated immune response.…”
Section: Bacterial Evs—another Source For Consideration?mentioning
confidence: 99%
“…Accordingly, massive production of both intestinal sIgA as well as serum IgG antibodies against EV-transmitted antigens was noted in mice that were orally immunized with three doses of chitosan-coated Campylobacter jejuni -derived EVs together with the induction of a specific cell-mediated immune response. Furthermore, after a subsequent intragastric challenge with C. jejuni , a significant reduction in the bacterial load and only slight histological changes in the cecal tissue was observed in immunized animals [ 47 ]. Similarly, four intragastric administrations of H. pylori -derived EVs with a cholera toxin as an adjuvant protected mice from H. pylori infection by activating the production of antibodies specific for EVs’ outer membrane protein [ 49 ].…”
Section: Bacterial Evs—another Source For Consideration?mentioning
confidence: 99%
“…Consequently, the estimation of the core VF proteins for subcellular location revealed that 47 proteins were cytoplasmic, 19 were located in the cytoplasmic membrane, one was in the outer membrane, three were unknown, and four were periplasmic ( Figure 3C ). It is known that outer membrane vesicles (OMVs) are a molecular complex consisting of lipopolysaccharides (LPS), outer membrane proteins, periplasmic proteins, lipids, and even cytoplasmic proteins, which are important vehicles for the simultaneous delivery of many effector molecules to host cells ( Cai et al, 2018 ; Singh et al, 2021 ). Exposed proteins are often attractive targets for vaccine design, but sometimes not all proteins must be exposed to the surface, including some periplasmic proteins present in OMV preparations, which may also elicit an immunogenic response ( Awanye et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposed proteins are often attractive targets for vaccine design, but sometimes not all proteins must be exposed to the surface, including some periplasmic proteins present in OMV preparations, which may also elicit an immunogenic response ( Awanye et al, 2019 ). Due to the role of OMVs in intestinal adhesion and invasion, and in regulating the dynamic interaction between host and pathogens, OMVs have become potential vaccine targets for a variety of intestinal pathogens ( Singh et al, 2021 ). Therefore, the bacterial cell surface and secreted proteins, usually located in the extracellular, periplasmic, and outer membranes, could be more effective as vaccine candidates or diagnostic targets.…”
Section: Resultsmentioning
confidence: 99%
“…The chitosan-nanoparticles were coated with outer-membrane vesicles and then evaluated in mouse model for induction of specific immune response against C. jejuni . The results indicated that intragastric delivery of chitosan-coated outer-membrane vesicles impart significant immune protection ( 166 ).…”
Section: Methicillin-resistant Staphylococcus Aureus ...mentioning
confidence: 99%